2017
DOI: 10.4239/wjd.v8.i5.172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycaemic management on diabetic kidney disease

Abstract: Hyperglycaemia contributes to the onset and progression of diabetic kidney disease (DKD). Observational studies have not consistently demonstrated a glucose threshold, in terms of HbA1c levels, for the onset of DKD. Tight glucose control has clearly been shown to reduce the incidence of micro- or macroalbuminuria. However, evidence is now also emerging to suggest that intensive glucose control can slow glomerular filtration rate loss and possibly progression to end stage kidney disease. Achieving tight glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 69 publications
(80 reference statements)
0
49
1
6
Order By: Relevance
“…In larger observational studies, diabetes has also been found as a predictor of progression to CKD Stage 5. 29 Thus, in the wider NSW CKD population that has lower rates of diabetes, DC may potentially delay TTD further compared to the results obtained in this study. Based on the study results, a post-analysis sample size calculation found the study to be adequately powered.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In larger observational studies, diabetes has also been found as a predictor of progression to CKD Stage 5. 29 Thus, in the wider NSW CKD population that has lower rates of diabetes, DC may potentially delay TTD further compared to the results obtained in this study. Based on the study results, a post-analysis sample size calculation found the study to be adequately powered.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, diabetes was found to be negatively associated with TTD (HR 1.81), with these patients commencing dialysis quicker than those without diabetes. In larger observational studies, diabetes has also been found as a predictor of progression to CKD Stage 5 . Thus, in the wider NSW CKD population that has lower rates of diabetes, DC may potentially delay TTD further compared to the results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Среди них процент больных, имевших и не имевших диагноз СД (вне зави-симости от типа терапии), был сопоставим в группах с физиологической и быстрой потерей почечной функции. Надо отметить, что, несмотря на прямую зависимость раз-вития и прогрессирования ХБП от степени компенсации СД, четкая связь выявляется при уровне гликированного гемоглобина >7 % [40][41][42]. Среди участников нашего исследо-вания с установленным диагнозом СД были больные, у которых гликемия была компенси-рована на протяжении всего периода наблю-дения, в т. ч. и на фоне соблюдения диеты, без гипогликемической терапии.…”
Section: Discussionunclassified
“…Негативное влияние протеинурии на ухуд-шение функции почек подтверждено резуль-татами многочисленных исследований и в настоящее время не подвергается сомнению [40,[42][43][44][45]. Так, по данным [46], для пациен-тов с СД, имеющих протеинурию, средняя динамика СКФ за 4 года наблюдения соста-вила -8,42 мл / мин, что было вдвое больше по сравнению с пациентами без протеинурии.…”
Section: Discussionunclassified
“…[8][9][10][11][12] Diabetic kidney disease occurs in patients with T2DM as a consequence of reduced kidney function, triggered by hypertensive nephrosclerosis and unresolved acute renal failure as the main culminating reasons. [13][14][15][16][17][18][19] Diabetic nephropathy is a diagnosis that refers to specific pathologic structural and functional changes seen in kidneys of patients with T2DM. These changes result in a clinical presentation that is characterized by proteinuria, hypertension, and progressive reductions in kidney function.…”
Section: Introductionmentioning
confidence: 99%